Pendapingan Pendistribusian Produk Usaha Mikro Kecil dan Menengah (UMKM) Dalam Upaya Peningkatan Penjualan di Desa Malangsari - Wahyudin Wahyudin; Helysia Ananda Pinem; Hafidz Naufal Ar-rabbani; Dhini Khasanah; Devi Melisabeth Bu Ulolo; Ardiatama Iedha Aradhea; Johannes Siburian; Dwi Pratiwi; Vinda Febryani; Angelita Ramadhani (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Entrepreneurship is one of the main drivers in improving the economy in Indonesia, especially through the Small and Medium Enterprises (MSME) sector. In Karawang Regency, efforts to support the growth of MSMEs are not only limited to providing training, but also comprehensive assistance from start to finish. The aim of this community service activity is to facilitate the development of MSMEs in the region. The methods applied include problem identification, training, mentoring, as well as monitoring and evaluation. The results of problem identification show that assistance in product distribution is a major need for MSMEs in Malangsari Village. Through this assistance, MSME players are given a better understanding of how to increase sales of their products. The results of monitoring and evaluation show that MSME actors in Malangsari Village have gained a good understanding of product distribution and have succeeded in increasing sales, and have begun to apply this knowledge in their businesses. The hope is that this community service effort can provide significant benefits for MSMEs in Malangsari Village, Pedes District, Karawang Regency..